Teacher Problems During the Implementation of Learning in the New Normal Era in Elementary Schools - Rahmawati, Nur (Universitas Pendidikan Ganesha, 2022)
The implementation of learning in the new normal era that involves teachers and students is not running optimally due to the impact of the covid-19 pandemic. It causes learning not to run optimally. This study aimed to analyze the problems and solutions faced by teachers in implementing learning in the new normal era of covid-19. The type of research is descriptive qualitative. The subjects of this study were one principal, four teachers, and two students. This research uses interview, observation, and documentation data collection techniques. The method used is collecting, reducing, presenting, and drawing conclusions. Based on the research results obtained, face-to-face learning is carried out systematically and follows the guidelines for implementing face-to-face learning in the new normal. The school has implemented it according to the health protocol procedures. In terms of implementing the teaching and learning process in the classroom, the material delivery is quite condensed and only conveys the essential points. Face-to-face learning activities usually continue even though government regulations limit time availability.